Vection Attenuates N400 Event-Related Potentials in a Change-Detection Task. (August 2019) - Stróżak, Paweł; Augustynowicz, Paweł; Ratomska, Marta; Francuz, Piotr; Fudali-Czyż, Agnieszka
The illusion of self-motion (vection) can affect human cognitive functioning, but little is known about the attentional mechanisms of this influence. In this study, event-related potentials were recorded, while participants ( N  = 23) performed a visual change-detection task in the S1–S2 matching paradigm, which was embedded in a visual stimulation pattern (VSP) that was static or moving. In the condition of moving VSP, participants had additionally to indicate whether they were sensing the illusion of self-motion (vection) or perceiving object-motion (no vection). For moving VSP, there were no differences in response accuracy or reaction times between conditions with vection and conditions without vection. Both for static and moving VSP, a series of event-related potentials time-locked to the onset of S2 was observed. N400 amplitudes from anterior–frontal electrodes were attenuated in conditions with vection as compared with conditions without vection. P3a and P3b amplitudes were also attenuated by vection but only in the subgroup of participants who had a high frequency of reporting vection. This shows that the illusion of self-motion disrupted the magnitude of an electrophysiological correlate of complex conflict detection. The potentials reflecting the direction of attention were not affected, unless individual differences in vection frequency were considered.